Ignatian Contemplative Pedagogy - Timothy P. Muldoon (Jesuit University Ignatianum in Krakow, 2022)
Research Objective: There is a growing literature about contemplative pedagogy in higher education, an approach to learning which prioritizes experiential, reflective practices meant to promote autonomy in learning. This essay will explore how Ignatian pedagogy, rooted in the 475-year tradition of Jesuit education, promotes a form of contemplative pedagogy especially apt for what this journal describes as the VUCA world (volatility, uncertainty, complexity and ambiguity). Research Problem and Methods: The essay addresses questions particularly relevant in the wake of the global pandemic: how can education promote greater self-care and self-knowledge? How can it promote greater compassion and care for others, especially the marginalized? How can it encourage people, especially the young, to develop practices that promote lifelong learning, flourishing, and responsibility? Process of Argumentation: The essay will review some of the burgeoning literature on contemplative pedagogy, and draw from the extensive literature about Ignatian pedagogy and especially the latter's strong emphasis on processes of reflection for the sake of just action. Research Results: The essay will show that there is a rich well of resources in the Ignatian spiritual and pedagogical traditions that promote contemplative pedagogy, and that application of these resources in contemporary educational and formational contexts will help promote lifelong learning, flourishing, and responsibility towards others. Conclusions, Innovations, and Recommendations: Educators are encouraged to introduce or develop contemplative practices such as journaling, guided meditations, focused conversations among peers, reflective critical writing, and others.